CARIBISKE SJÆLEANLIGGENDER - efter Fock - Rivière, Peter (Tidsskriftet Antropologi, 1997)
Peter Riviére: Carib Soul Matters - Since Fock When it appeared in 1963 Niels Fock’s Waiwai marked the beginning of a new age in the ethnography of the peoples of Guiana. This study will examine how far what Fock reported concerning Waiwai ideas about the soul is to be found among other Caribspeaking peoples of the region. After a summary of the Waiwai material, the notions of four other cases (Trio, Maroni River Caribs, Pemon and Kapon, and Yekuana) are looked at in tum. Each case exhibits both similarities and differences, but overall there is a high degree of convergence. In every case there is the idea of a soul(s) that goes, at death, to an etemal resting place and of another soul(s) that remains on earth, often to haunt the living. A point that the Trio material raises is the importance of the name as the bridge between the soul and body of the living person. This theme is not well developed in other works although it is hinted at by Fock himself with regard to the Waiwai. Elsewhere in Amazonia, however, the notion of the name as a vital component of the person or as an aspect of the soul has been frequently recorded. Two examples are adduced and it is suggested that this subject requires further exploration among the Carib-speaking peoples Guiana.